The G285S mutation in nsP1 is sufficient to render Sindbis virus as a stable vector for gene delivery - Shi, Xiangwei; Sun, Kangyixin; Hu, You; Wang, Qinghan; Liao, Guoyang; Li, Li; Wen, Pengjie; Wong, Leo E.; Jia, Fan; Xu, Fuqiang (Frontiers in Microbiology, 2023)
Neuroscience, gene therapy, and vaccine have all benefited from the increased use of viral vectors. Sindbis virus (SINV) is a notable candidate among these vectors.However, viral vectors commonly suffer from a loss of expression of the transgene, especially RNA viral vectors. In this study, we used a directed evolution approach by continuous passage of selection to identify adaptive mutations that help SINV to stably express exogenous genes. As a result, we found two adaptive mutations that are located at aa 285 (G to S) of nsP1 and aa 422 (D to G) of nsP2, respectively. Further study showed that G285S was sufficient for SINV to stabilize the expression of the inserted gene, while D422G was not. Combined with AlphaFold2 and sequence alignment with the genus Alphavirus, we found that G285S is conserved. Based on this mutation, we constructed a new vector for the applications in neural circuits mapping. Our results indicated that the mutant SINV maintained its anterograde transsynaptic transmission property. In addition, when the transgene was replaced by another gene, granulocyte-macrophage colony-stimulating factor (GM-CSF), the vector still showed stable expression of the inserted gene. Hence, using SINV as an example, we have demonstrated an efficient approach to greatly augment the gene delivery capacity of viral vectors, which will be useful to neuroscience and oncolytic therapy.